2021
DOI: 10.3390/jcm10122678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Home-Based Lifestyle Intervention Program on Cardiometabolic Health in Breast Cancer Survivors during the COVID-19 Lockdown

Abstract: This study aimed to evaluate the cardiometabolic effects of a home-based lifestyle intervention (LI) in breast cancer survivors (BCSs) during the COVID-19 lockdown. In total, 30 BCSs (women; stages 0–II; non-metastatic; aged 53.5 ± 7.6 years; non-physically active; normal left ventricular systolic function) with a risk factor for recurrence underwent a 3-month LI based on nutrition and exercise. Anthropometrics, Mediterranean diet adherence, physical activity level (PAL), cardiorespiratory fitness (VO2max), ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 96 publications
1
36
0
Order By: Relevance
“…One of the hallmarks of cancer cells is the reprogramming of cellular metabolism in response to the increased energy demand necessary to support proliferation and tumor growth. This process forces cells to depend on glucose as fuel and glycolysis to generate NADPH and ATP instead of the normal oxidative phosphorylation processes, a phenomenon known as the “Warburg effect” [ 6 , 7 ]. Glucose enters cancer cells through specific transporters.…”
mentioning
confidence: 99%
“…One of the hallmarks of cancer cells is the reprogramming of cellular metabolism in response to the increased energy demand necessary to support proliferation and tumor growth. This process forces cells to depend on glucose as fuel and glycolysis to generate NADPH and ATP instead of the normal oxidative phosphorylation processes, a phenomenon known as the “Warburg effect” [ 6 , 7 ]. Glucose enters cancer cells through specific transporters.…”
mentioning
confidence: 99%
“…The effectiveness of home-based intervention during a pandemic was also confirmed by Natalucci et al, who indicated that a 3-month home-based lifestyle intervention focused on a Mediterranean diet and aerobic exercise significantly reduced echocardiographic signs of diastolic dysfunction and improved autonomic function. In addition, there were significant improvements in BMI, cardiorespiratory fitness, metabolic and inflammatory parameters [ 39 ]. Our study also confirmed that online classes could both improve patients’ fitness and positively affect their psychological well-being ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of daily physical activities such as walking and biking during lockdown could also have contributed to the deterioration of lung function [ 36 ]. The patients did not undergo cardiometabolic lifestyle intervention to mitigate the inactivity [ 37 ]. The drop in LVEF seen in 2020 also suggests the possibility of undiagnosed COVID-19 myocarditis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%